Migrations agricoles, dynamique de dégradation du couvert forestier et émergence de systèmes agro-forestiers à base de cacaoyer dans la Sous-préfecture de Bléniméouin (Ouest-ivoirien) - Diané Lucien, ADOU; Styvince Romaric, Dr. KOUAO N'kpomé; Mel, TROTSKY (International Journal of Scientific Research and Management (IJSRM), 2023)
Expansion of cultivation camps, dynamics of degradation of forest cover and emergence of cocoa-based agro-forestry systems in the Sub-prefecture of Bléniméouin (Western Côte d'Ivoire)The Sub-prefecture of Bléniméouin is part of the western forest region of Côte d'Ivoire, home to the new pioneer fronts of the country for the past two decades. Due to its natural potential (maintenance of a few scraps of primary forest, hot and humid climate, etc.) and its very dynamic plantation economy, this territory is experiencing strong land pressure which results in agricultural migrations and the expansion of cultivation camps. Alongside the dwindling of land reserves, new agroforestry practices have been emerging since the end of the 2010-2020 decade. Thus, the objective of this study is to analyze the agrarian and landscape changes induced by the expansion of cultivation camps in the said Sub-prefecture. To achieve this objective, a multi-date analysis based on the exploitation of Landsat images (TM 1980, ETM+ 2000 and Oli/Tirs 2021) coupled with S.I.G was adopted and supplemented by field observations. The results reveal significant regressive forest cover dynamics. From 1980 to 2021, the area of ​​primary forest has increased from 6499 ha or 29% of the space to 1360 ha or 6%. The area lost by the forest has been converted mainly into areas of perennial crops (60%), food crops (37%) and bare soils (3%). Faced with land saturation, rural people are developing new agro-forestry techniques combining cashew, cocoa and rubber orchards in order to create more ecological conditions beneficial to all kinds of crops (food crops and perennials).